Practical Electrical and Current Signature Analysis of Electrical Machinery and Systems - Penrose, Howard (Success by Design, 2022)
An essential working tool for understanding the application of electrical and current signature analysis to test commercial, industrial and utility systems from servo motors to wind turbines.